Warfarin Treatment Is Associated to Increased Internal Carotid Artery Calcification - Nuotio, Krista; Koskinen, Suvi M.; Mäkitie, Laura; Tuimala, Jarno; Ijäs, Petra; Heikkilä, Hanna M.; Saksi, Jani; Vikatmaa, Pirkka; Sorto, Pia; Kasari, Sonja; Paakkari, Ilari; Silvennoinen, Heli; et al. (Frontiers in Neurology, 2021)
Background: Long-term treatment with the vitamin K antagonist warfarin is widely used for the prevention of venous thrombosis and thromboembolism. However, vitamin K antagonists may promote arterial calcification, a phenomenon that has been previously studied in coronary and peripheral arteries, but not in extracranial carotid arteries. In this observational cohort study, we investigated whether warfarin treatment is associated with calcification of atherosclerotic carotid arteries. Methods: Overall, 500 consecutive patients underwent carotid endarterectomy, 82 of whom had received long-term warfarin therapy. The extent of calcification was assessed with preoperative computed tomography angiography, and both macroscopic morphological grading and microscopic histological examination of each excised carotid plaque were performed after carotid endarterectomy. Results: Compared with non-users, warfarin users had significantly more computed tomography angiography-detectable vascular calcification in the common carotid arteries (odds ratio 2.64, 95% confidence interval 1.51–4.63, P < 0.001) and even more calcification in the internal carotid arteries near the bifurcation (odds ratio 18.27, 95% confidence interval 2.53–2323, P < 0.001). Histological analysis revealed that the intramural calcified area in plaques from warfarin users was significantly larger than in plaques from non-users (95% confidence interval 3.36–13.56, P = 0.0018). Conclusions: Long-lasting warfarin anticoagulation associated with increased calcification of carotid atherosclerotic plaques, particularly in locations known to be the predilection sites of stroke-causing plaques. The clinical significance of this novel finding warrants further investigations.